Implementasi Digitalisasi Simonav Dalam Meningkatkan Efektivitas Pemeliharaan Kapal Negara Kenavigasian Pada Distrik Navigasi Tipe B Tanjung Priok - Lestari, Diyah Dewi; Barasa, Larsen; Cahyadi , Tri (Jurnal Sosial Teknologi, 2025)
This study aims to analyze the implementation of digitalization through the Maritime Navigation Aid Vessel Operational and Maintenance Monitoring Information System (SIMONAV) in enhancing the effectiveness of government vessel maintenance in the Tanjung Priok Type B Navigation District. Digitalization through SIMONAV is expected to facilitate the monitoring of vessel operations and maintenance, as well as accelerate the reporting of damages and maintenance procedures. This research employs a qualitative approach, gathering data through interviews, observations, and documentation. The results indicate that the implementation of SIMONAV has improved efficiency in managing government vessel maintenance by providing real-time access to information, minimizing administrative errors, and expediting decision-making related to vessel maintenance. Moreover, this application also supports coordination between relevant parties in monitoring and maintaining the vessels. Overall, SIMONAV plays a crucial role in improving the effectiveness of government vessel maintenance in the Tanjung Priok Type B Navigation District.